Cutaneous carcinosarcoma: a series of six cases and a review of the literature. (18th November 2016) - Clark, Joshua J.; Bowen, Anneli R.; Bowen, Glen M.; Hyngstrom, John R.; Hadley, Michael L.; Duffy, Keith; Florell, Scott R.; Wada, David A.
Abstract : Background: Cutaneous carcinosarcoma is a rare tumor with distinct malignant epithelial and mesenchymal cell populations. The histologic subtypes of epithelial and mesenchymal components in cutaneous carcinosarcoma are variable, as an assortment of carcinomatous and sarcomatous patterns have been described in the literature. Methods: Clinical information was obtained from patient charts and archival slides were retrieved and reviewed. Results: We present a novel series of six distinct cases of cutaneous carcinosarcoma and review the literature. Our cases consisted of basal cell, pilomatrical, squamous cell, and trichoblastic variants. These cases occurred in elderly men on sun exposed skin with treatment and follow up was available for 4 of 6 cases. The four cases were treated with Mohs micrographic surgery with mean follow up of nine months. Conclusion: We report six cases of cutaneous carcinosarcoma with distinctive clinical and histologic characterization not previously described in a single series.